The Utilization of A3S Information-Inferencing Fusion Method for Nation Defense - Arwin Datumaya Wahyudi.S; Adang Suwandi Ahmad; Aciek Ida Wuryandari; Jaka Sembiring (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2009)
Decision-making is the most critical phase in Observe, Orient, Decide, and Act (OODA) defense decisioncycle. If the decision made is correct regarding the current situation, then it can minimize the possibility of loss.The contradiction situation will occur if the incorrect decision is made. The correctness of the decision dependsof the quality on information delivered from Orient(ation) phase that will be used as the basis for decisionmaking.Meanwhile, in defense applications the process of decision-making plays a very important roleespecially if the time is the most affecting factor. Such an application is nation defense system in defending ourcountry’s nation sovereignty in air, sea, and land. Therefore, the faster the decision is made, the earlier thesystem can perform anticipations to any nation defense intrusion. For this purpose, in this paper we address theutilization of A3S (Arwin-Adang-Aciek-Sembiring) information-inferencing fusion for accelerating theinformation processing and obtaining good comprehensive information quality that will be used as the basis forstrategic decision-making for nation defense.Keywords: A3S, information-inferencing fusion, nation defense, OODA, strategic decision-making